2014
DOI: 10.1007/s10266-014-0169-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti surface treatments with silane and arginylglycylaspartic acid peptide on bone cell progenitors

Abstract: Achieving optimal aesthetic appearance is a major objective in dental implant design, and the interaction between the materials and the bone cell progenitors is an important factor in the attainment of this objective. In this study, a novel concept was evaluated by varying the surface modifications on titanium (Ti). Different levels of roughness can be attained by machine grinding (M), sand blasting, and acid etching (SLA) of the samples. The behavior of bone cell progenitors (D1) on the surfaces of Ti disks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…While Coombe et al 19 repeatedly reported that laser irradiation did not show a significant effect on the ALP activity, Cho et al 20 found that implant surfaces treated with laser show higher removal torque than turned implant surfaces. 21 Francisley et al suggested that laser-treated surface had regular cavities similar to honeycomb and showed excellent osseintegration. 22 The reason was that primary stability of implants was initially gained from mechanical fixation in the peripheral bone and then from bone remodeling, which occurred during the 2 nd and 4 th weeks after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…While Coombe et al 19 repeatedly reported that laser irradiation did not show a significant effect on the ALP activity, Cho et al 20 found that implant surfaces treated with laser show higher removal torque than turned implant surfaces. 21 Francisley et al suggested that laser-treated surface had regular cavities similar to honeycomb and showed excellent osseintegration. 22 The reason was that primary stability of implants was initially gained from mechanical fixation in the peripheral bone and then from bone remodeling, which occurred during the 2 nd and 4 th weeks after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZnO thin films have their surface terminated by hydroxyl groups that can be functionalized by several molecules such as carboxylic acids, esters, acid chlorides and others bifunctional molecules [21], originating an effective control of the surface properties that can result in a more bioactive surface with enhanced corrosion T resistance. Previous studies have indicated that silane treatment on various substrate surfaces can promote cell adhesion, cell proliferation, and hydroxyapatite nucleation to improve osteoblast's adhesion [22,23]. Polyethylene glycol have been used on surface functionalization to obtain anti-infective medical implants because it can reduce the bacterial adhesion [24].…”
Section: Introductionmentioning
confidence: 99%